Salt Sensitivity Determined From Capillary Blood - Hans Oberleithner; Marianne Wilhelmi (Karger Publishers, 2016)
Background/Aims: A significant rise of blood pressure in response to a given salt load is a weak indication of high salt sensitivity, supposed to foster the development of arterial hypertension and related diseases in later life. In search of an alternative method we recently developed the salt blood test (SBT), a new concept for quantifying salt sensitivity (SS). Based on this concept, namely that red blood cells (RBC) report on salt sensitivity, the SBT-mini was developed. Methods: The SBT-mini utilizes a droplet of capillary blood mixed with a 'smart' Na+ cocktail. Red blood cells (RBC) of this mixture are allowed to sediment by gravity in a glass tube. SS is quantified by measuring RBC sedimentation rate. 90 healthy volunteers (39 males, 51 females; mean age: 23±0.5 years) were evaluated and 'standard values' for males and females were derived. Results: Sodium buffer capacity of female blood is about 20 % smaller as compared to male blood due to the lower hematocrit of females. SS of an individual is related to the mean standard value (set to 100 %) of the respective male/female cohort. High SS (> 120 %) has been found in 31 % of males and 28 % of females. Conclusions: SS can be estimated derived from the individual RBC sodium buffer capacity as measured by the SBT-mini. About one third of a healthy test cohort exhibits a high sensitivity to salt. Reduction of sodium consumption to at least two grams per day (equals five grams of NaCl per day as suggested by the WHO) is recommended, particularly for individuals with high salt sensitivity.